Development of History Learning Modules Based on Traditional Values and Local Wisdom in Sambas - Januardi, Arif; Superman, Superman (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This research addresses the lack of contextual historical learning materials that incorporate local culture, which often leads to students' low interest and limited understanding of regional history. Therefore, the study aims to develop a valid and effective history learning module based on traditional values and local wisdom of Sambas Regency. Using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model, the study involved validation by 3 material and media experts, followed by a limited trial on 35 eleventh-grade students at SMA Negeri 1 Sambas. The validation results showed a high level of validity with an average score of 93.03%. Effectiveness testing was conducted using the Normalized Gain (N-Gain) method, resulting in a score of 0.61, categorized as medium effectiveness based on Hake's (1999) criteria. The module integrates traditional values such as  saprahan,  tepung tawar, and Sambas Malay poetry to make history learning more engaging and locally relevant. The findings show that the module increases student participation and understanding of regional history. Therefore, it is recommended as a meaningful teaching alternative that also supports cultural preservation. Further improvements are needed to enhance interactivity and digital integration.